2020
DOI: 10.1002/cnma.202000110
|View full text |Cite
|
Sign up to set email alerts
|

Greatly Enhanced Electrocatalytic N2 Reduction over V2O3/C by P Doping

Abstract: As a carbon‐neutral alternative technology to the Haber−Bosch process, electrochemical N2 reduction enables eco‐friendly NH3 synthesis under ambient conditions but requires electrocatalysts to drive the N2 reduction reaction (NRR). Here, P doping is proposed as a valid strategy to greatly increase the NRR activity of the V2O3/C shuttle‐like nanostructure. In 0.1 M Na2SO4, the NH3 yield of original V2O3/C is 12.6 μg h−1 mg−1cat. and a Faraday efficiency (FE) of 6.06% at −0.45 V and −0.25 V vs. reversible hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Note that other oxide/nanocarbon materials have been reported for this reaction. For example, -V 2 O 3 /C P-doped, [134] showing a NH 3 formation rate of 22.4 µg h −1 mg cat −1 at −0.35 V versus RHE, and an FE of 13.8% at −0.25 V versus RHE -oxygen vacancy-rich NiCo 2 O 4 on hollow N-carbon polyhedra [135] showing a NH 3 formation rate of 17.8 µg h −1 mg −1 with Faradaic efficiency of 5.3% -vanadium carbide nanoparticles/carbon sphere [136] showing a NH 3 formation rate of 34.6 µg h −1 mg cat −1 and Faradaic efficiency of 12.2% at −0.40 V versus RHE -copper supported on activated carbon functionalized with sulfonate groups (Cu/AC-S), [137] showing a NH 3 formation rate of 9.7 µg h −1 mg −1 and a Faradaic efficiency of 15.9% at −0.3 V versus RHE.…”
Section: Role Of the Creation Of Metal Oxide(hydroxide)/nanocarbon Boundaries And In Situ Dynamicsmentioning
confidence: 99%
“…Note that other oxide/nanocarbon materials have been reported for this reaction. For example, -V 2 O 3 /C P-doped, [134] showing a NH 3 formation rate of 22.4 µg h −1 mg cat −1 at −0.35 V versus RHE, and an FE of 13.8% at −0.25 V versus RHE -oxygen vacancy-rich NiCo 2 O 4 on hollow N-carbon polyhedra [135] showing a NH 3 formation rate of 17.8 µg h −1 mg −1 with Faradaic efficiency of 5.3% -vanadium carbide nanoparticles/carbon sphere [136] showing a NH 3 formation rate of 34.6 µg h −1 mg cat −1 and Faradaic efficiency of 12.2% at −0.40 V versus RHE -copper supported on activated carbon functionalized with sulfonate groups (Cu/AC-S), [137] showing a NH 3 formation rate of 9.7 µg h −1 mg −1 and a Faradaic efficiency of 15.9% at −0.3 V versus RHE.…”
Section: Role Of the Creation Of Metal Oxide(hydroxide)/nanocarbon Boundaries And In Situ Dynamicsmentioning
confidence: 99%
“…Some studies have shown that defect engineering can regulate and modify the local coordination environment of electrocatalysts and promote intrinsic activity. Recent advances in defect engineering of nanostructured electrocatalysts, including vacancy, heteroatom doping, [16] facet engineering and surface modification, are summarized. Lai et al.…”
Section: Figurementioning
confidence: 99%
“…is because of their unmatched structural types, multiphase states, and easy modification. 35 , 36 As shown in our previous work, 37 V 2 O 3 -based CEs had been successfully prepared using VOCl 3 as metal precursors with the urea–metal route. The DSSCs using V 2 O 3 CEs showed a decent PCE value of 5.40%.…”
Section: Introductionmentioning
confidence: 84%